PENGARUH KECERDASAN EMOSIONAL, KOMITMEN ORGANISASI, DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR TERHADAP KINERJA KARYAWAN PT METROPOLITAN RETAILMART SOLO BARU - Erika Yulia Agustin, Untung Sriwidodo & Suprayitno (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2017)
PT Metropolitan Retailmart Solo Baru is a retail company in the field of fashion,hearts run company trying to improve the operational activities of employees boardingcosts. The purpose of research is to analyze the significance of the influence ofemotional intelligence, organizational commitment and Organizational CitizenshipBehavior on employee performance as well as the dominant variable influence onemployee performance. Emotional intelligence significantly influence employeeperformance. Organizational commitment significantly influence employeeperformance. Organizational Citizenship Behavior significant influence on employeeperformance. Organizational commitment variables are variables that dominantinfluence on employee performance. F test results obtained p-value of 0,000 < 0,05means that the model used to test the effect of independent variables of emotionalintelligence, organizational commitment and Organizational Citizenship Behavior onemployee performance is appropriate. The results of the analysis of the coefficient ofdetermination is obtained is known that the influence exerted by the independentvariable of emotional intelligence, organizational commitment and OrganizationalCitizenship Behavior of the dependent variable is the performance of employees is55,5% while the rest (100% - 55,5%) = 44,5% influenced by other factors beyond thevariables studied.Keywords: emotional intelligence, organizational commitment, organizationalcitizenship behavior, employee performance